The clinical relevance of adiposity when assessing muscle health in men treated with androgen deprivation for prostate cancer. Issue 5 (8th May 2019) - Owen, Patrick J.; Daly, Robin M.; Dalla Via, Jack; Mundell, Niamh L.; Livingston, Patricia M.; Rantalainen, Timo; Fraser, Steve F.
Abstract: Background: Androgen deprivation therapy (ADT) for prostate cancer (PCa) may prospectively decrease absolute lean mass (LM) and increase absolute fat mass (FM). Given that estimates of LM by dual‐energy X‐ray absorptiometry may be overestimated in obese people, this study examined the influence of adiposity on muscle health in men treated with ADT for PCa. Methods: This cross‐sectional study examined the influence of adiposity on total and appendicular LM (ALM), muscle cross‐sectional (CSA), and muscle strength in 70 men treated with ADT [mean (standard deviation) age, 71 (6) years] for PCa compared with age‐matched PCa ( n = 52) and healthy controls ( n = 70). Total body LM, FM and ALM, and 66% tibia and radius muscle CSA were quantified by dual‐energy X‐ray absorptiometry and peripheral quantitative computed tomography, respectively. ALM was further divided by height (m 2 ) or body mass index, with muscle CSA expressed as a per cent of total limb CSA. Upper and lower body and back (three‐repetition maximum and dynamometry) muscle strength were expressed per kilogram of body weight. Results: On average, ADT‐treated men had 4.4–6.4 kg greater FM compared with controls ( P ≤ 0.014) and there were no differences in total body or ALM. Total body per cent LM and ALMBMI were 3.8–5.4% ( P ≤ 0.001) and 7.8–9.4% ( P ≤ 0.001) lower, respectively, in ADT‐treated men compared with both controls. Percentage muscle CSA at both sites and muscle strength (except leg) were 3.0–6.0% ( P ≤ 0.031) and 15–17% ( P ≤ 0.010) lower, respectively, in ADT‐treated men compared with both controls. Conclusions: The findings from this study indicate muscle mass, size, and strength are compromised in men treated with ADT after accounting for their increased adiposity or body size.